2020
DOI: 10.1016/j.bpj.2019.11.1448
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Stress May Impact the Formation of Stress Granules

Abstract: The advent of molecular tension probes for real-time mapping of piconewton forces in living systems has had a major impact on mechanobiology. For example, DNA-based tension probes have revealed roles for mechanics in platelet, B cell, T cell, and fibroblast function. Nonetheless, imaging shortlived forces transmitted by low-abundance receptors remains a challenge. This is a particular problem for mechanoimmunology where ligand-receptor bindings are short lived, and a few antigens are sufficient for cell trigge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Emerging evidence is revealing that LLPS plays essential roles in mechanosensing for regulating the mechanobiological signal coupling and mechanosensitivity of cells. For example, mechanical stretch regulates the SGs formation in smooth muscle cells thus affecting the protein translation and cell physiology (40). Another research revealed that biomacromolecule LLPS facilitates the assembly and organization of matured FAs, thus allowing for efficient mechano-transduction and cell migration.…”
Section: Regulation Of Cellular Mechanotransductionmentioning
confidence: 99%
“…Emerging evidence is revealing that LLPS plays essential roles in mechanosensing for regulating the mechanobiological signal coupling and mechanosensitivity of cells. For example, mechanical stretch regulates the SGs formation in smooth muscle cells thus affecting the protein translation and cell physiology (40). Another research revealed that biomacromolecule LLPS facilitates the assembly and organization of matured FAs, thus allowing for efficient mechano-transduction and cell migration.…”
Section: Regulation Of Cellular Mechanotransductionmentioning
confidence: 99%